An Analytical study to determine the Prevalence and Factors associated with Late first Antenatal Care Visit among Pregnant Women at Mukono General Hospital, Mukono District. - Musitwa , Moses (Student’s Journal of Health Research Africa, 2022)
Background: A study was carried out to determine the prevalence and factors associated with late first antenatal care visits among pregnant women at Mukono General Hospital, Mukono District. Methodology: The study design was descriptive and cross-sectional and it employed both quantitative and qualitative data collection methods. A sample of 60 respondents was selected using a purposive sampling procedure and an interview guide was used to collect data. Results: The proportion of pregnant mothers who timely initiated ANC visits was 40 (66.7%) attended the first ANC visit between 4 – 6 months of pregnancy, 40 (66.7%) had attended ANC once during the current transition, 24 (40%) reported lack of awareness/knowledge as a reason for failing to timely initiate ANC visits, followed by 16 (26.7%) who reported lack of support, 12 (20%) reported that they did not feel the need to attend early. Respondents also faced various maternal factors as 40 (66.7%) respondents reported that they did not attend ANC in the last pregnancy, 50 (83.3%) did not receive advice before starting ANC visits, 60 (100%) did not have other means of testing current pregnancy, 40 (66.7%) reported not having adequate knowledge about ANC services, 40 (66.7%) reported that they sometimes had to get their husband`s approval to start ANC visits, 42 (70%) rated the previous experiences of services utilization as good. Conclusion: Respondents faced various socio-demographic and maternal factors which have led to a low proportion of mothers attending the 1st ANC visit in the first semester as recommended. Recommendations: Including improving efficiency and reducing waiting time, improving customer care, more support, and health education about ANC among others.